PEMBUKUAN SECARA PRAKTIS DALAM PENGELOLAAN KEWIRAUSAHAAN EMPING MLINJO DI DESA WONOKERSO, LIMPUNG KABUPATEN BATANG - Agung Wibowo; Caecilia Sri Haryanti; Parju Parju; Nurchayati Nurchayati; Janti Janti; Setyobudi Setyobudi (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
Mlinjo chip entrepreneurs in Wonokerso Village encountered difficulties managing finances systematically without adequate bookkeeping practices, hindering accurate profit-loss assessment. This community engagement program sought to enhance practical bookkeeping capabilities among fifteen members of